Why are saving rates of urban households in China rising? - Marcos Chamon; Eswar Prasad (Institute for the Study of Labor (IZA), 2007)
From 1995 to 2005, the average urban household saving rate in China rose by 8 percentage points, to about one quarter of disposable income. We use household-level data to explain why households are postponing consumption despite rapid income growth. Tracing cohorts over time indicates a virtual absence of consumption smoothing over the life cycle. The age profile of savings has an unusual U-shaped pattern, with saving rates being the highest among the youngest and oldest households. We find that financial underdevelopment, as reflected in constraints on borrowing and low returns on financial assets, partially accounts for this pattern. Moreover, overall saving rates have increased across all demographic groups. We argue that this can be explained by the rising private burden of expenditures on housing, education, and health care.
Keywords: D12; 330; Household savings; age and cohort profiles of savings; borrowing constraints; precautionary savings; financial development; demographics; Sparen; Privater Haushalt; Stadtbevölkerung; Einkommenshypothese; China